Photoelectrocatalytic oxidation of moxifloxacin on NiWO4-CoWO4 homojunction photoanode - Silva, Emily; Sousa, Renato; Neto, Geraldo; Costa, Antonio; Costa, Maria; Costa, Gilson; Silva, Rejane; da Silva Santos , Reginaldo (XIV Encontro de Catálise do Norte, Nordeste e Centro-Oeste, 2024)
Advanced Oxidative Processes (AOP) consist of the use of radial hydroxyls (•OH) to completely mineralize organic contaminants such as dyes and drugs, converting them into CO2 and water. In heterogeneous photocatalysis, TiO2 is still the most investigated material as it presents advantages that include low cost and high chemical stability. However, TiO2 has photoactivity only under radiation with λ < 380 nm. In this context, colored oxides such as cobalt tungstate (CoWO4) and nickel tungstate (NiWO4) become attractive semiconductors as they are capable of absorbing light in the visible region of the spectrum [1]. In addition, semiconductor junction strategy has been used to minimize charge recombination electron-hole [2]. In this work we present the results of studies carried out with films (photoelectrodes) formed by the homojunction of CoWO4 and NiWO4. The n-type behavior of the films allowed their application as a photoanode for oxidation of the antibiotic Moxifloxacin (MOX), a broad-spectrum antibiotic that belongs to the fluoroquinolone class. MOX is used to treat a variety of bacterial infections. However, the presence of MOX as a pollutant in wastewater can promote the emergence of bacteria resistant to this drug. Thus, the removal of MOX by AOP is an alternative to prevent the emergence of superbugs. CoWO4 and NiWO4 oxides deposited as films on FTO-glass were obtained by the polymeric precursor method. XRD measurements revealed that both oxides present a monoclinic phase. The optical characterization showed that the junction of materials shifted the light absorption region to longer wavelengths (Fig. 1a), suggesting greater use of visible light for homojunction film. Chronopotentiometric measurements confirmed the n-type behavior of the material. Film with homojunction of the FTO|NiWO4-CoWO4 showed charge separation superior to the FTO|CoWO4-NiWO4 configuration. Energy band diagram shaped the favorable charge flow for the FTO|NiWO4-CoWO4 junction. This homojunction presented photocurrents of 25 µA cm-2 (vs Ag/AgCl) (Fig. 1b). In photoelectrocatalysis, the application of potential to the homojunction electrode favored the charge separation process and increased the MOX removal efficiency, reaching 30% in 180 min (Fig. 1c). This result is superior to those observed for photocatalysis obtained in the absence of potential application (bias potential). Thus, the strategy of combining two colored tungstate semiconductors and the application of an external polarization potential (FHE) proved to be more efficient in treating water contaminated by MOX.